ACCOUNTING STUDENT PERCEPTIONS OF ETHICS IN FINANCIAL STATEMENT PREPARATION AND THE EFFECTS OF ACCOUNTING SCANDALS - Ishmah Muthiah; Elis Mediawati (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This research aims to find out the differences in perception regarding the ethics of thepreparation of financial statements and accounting scandals and businesses in the accountingprofession between lower-level accounting students and top-level accounting students. Thepopulation in this study is students of Accounting Study Program S1 Bandung lower level andtop level of 106 people with purposive sampling techniques. Data collection techniques usingquestionnaires. The hypothesis test in this study used an average independent T-test with thehelp of SPSS Statistics 25 software. The results of this study show that on the ethics of financialreport preparation, only misrepresentation factors do not have significant differences betweenlower-level students and top-level students. And there is a difference in perception on theunderstanding of the Accounting scandal between lower-level students and top-level students.